Analysis of Spontaneous Raman and Rayleigh Scatterings in Distributed Fiber Raman Amplification Systems Based on a Random Distribution Model - Qiguang Feng; Wei Li; Liyan Huang (IEEE Photonics Journal)
The properties of light wave propagation with stochastic scattering in a fiber are particularly attractive because of their influence in various applications. Although stochastic scattering in fibers is of great significance, until now, no accurate theoretical model has described the randomness of the distributions and variations in scattering since the scattering sources are regarded as centralized or homogeneously distributed. In this paper, we proposed a model to analyze the random variation in scattering with time and location. Then, we employed the model to simulate stochastic scattering in distributed fiber Raman amplification (FRA) systems, including Rayleigh backscattering and spontaneous Raman scattering, which are crucial limitations of the distributed FRA systems. The simulations agreed well with our experimental measurements, proving that our model efficiently described stochastic scattering spectra and distributions in FRAs. Our theory accurately analyzed the distribution and evolution of scattering along the fiber and is a promising tool for optimizing the performance of distributed fiber systems, especially systems with distributed amplification such as fiber communication systems, random feedback fiber lasers, and fiber sensors.